Retargeting as a key to revenue growth in e-commerce - Baranyk, Pavel (2014)
The thesis gives an insight into the field of online marketing with a special focus on acquisition channels analysis and retargeting. The goals of this thesis are to introduce the most frequently used acquisition channels with focus on retargeting, carry out analyses of their performance in case of selected e-shop Feedo.cz and confirm pivotal role of retargeting in driving revenue growth of the company. The study was principally based on primary research of data and personal interviews with international online marketing experts that resulted into a unique and comprehensive overview of retargeting types and specific techniques. The analyses conclude that retargeting is not the biggest revenue growth driver even if it is a very important part of multichannel approach. Analyses of acquisition channels if further enriched by recommendations for further development of the company and its online marketing strategy.